The impact of effort-oriented epistemological beliefs on mentoring support. Issue 5 (13th July 2015) - Weinberg, Frankie J.; Mulki, Jay P.; Lankau, Melenie J.
Abstract : Purpose: – The purpose of this paper is to examine the role of mentor beliefs about effort related to the knowledge and learning process on their extent of mentoring at work, and to determine the role that the mentor's perception of psychological safety plays in tempering this relationship. Design/methodology/approach: – This study was conducted at an 820-member organization maintenance and operations organization consisting of a number of professions in which apprenticeship-style learning is prevalent. Data collection resulted in 570 members self-identifying as having mentored a less experienced colleague. Confirmatory factor analysis was used to confirm that the measurement instrument represents one unified factor, and a structural equation modelling approach was used to assess the relationships among the study's latent variables. Findings: – Results reveal that mentors who hold sophisticated effort-oriented beliefs are more likely to offer psychosocial support to their protégés. Further, although the relationship between effort-oriented beliefs and vocational support is not significant, the mentor's perception of a psychologically safe work environment significantly moderates both sets of relationships. Research limitations/implications: – As approximately 88 per cent of respondents work in service, as opposed to administrative groups, caution should be exercised in generalizing this study's findings to the general workforce population. Further, the present study did not differentiate mentors who identified a current or previous subordinate as their protégé from those whose protégés were not a subordinate, nor did the authors differentiate formal from informal mentoring relationships. Thus, further investigation is needed to determine whether our hypothesized relationships differ in any unique manifestations of mentoring relationships at work. Practical implications: – By providing a better understanding of the relationship between effort-oriented beliefs and mentoring at work, this study may help in the design of more effective mentoring relationships and ultimately enhance knowledge management and workplace learning. Originality/value: – There is no previous research that investigates how one's cognitions about the effort associated with the knowledge and learning process, in particular, influence mentoring at work. This study provides a model for understanding and developing enhanced mentoring relationships, which are considered a critical element of organizational learning.